Adverse and Allergic Reactions to Drugs - Epstein, Norman (1975)
Six major mechanisms by which adverse reactions to drugs can occur are outlined, with special reference being made to drug allergy. The article also covers diagnostic procedures, factors influencing development of drug allergy, prevention of adverse reactions, and treatment of immediate allergic response. Physicians are urged to convey their findings to the Drug Adverse Reporting Program in Ottawa, while patients are encouraged to contact the Canadian Medic-Alert Foundation for the appropriate tag.